1995
DOI: 10.1172/jci117768
|View full text |Cite
|
Sign up to set email alerts
|

Cross-resistance between cisplatin, antimony potassium tartrate, and arsenite in human tumor cells.

Abstract: Cross-resistance between cisplatin (DDP) and metalloid salts in human cells was sought on the basis that mechanisms that mediate metalloid salt cross-resistance in prokaryotes are evolutionarily conserved. Two ovarian and two head and neck carcinoma cell lines selected for DDP resistance were found to be cross-resistant to antimony potassium tartrate, which contains trivalent antimony. The DDP-resistant variant 2008/A was also cross-resistant to arsenite but not to stibogluconate, which contains pentavalent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 31 publications
(24 reference statements)
1
30
1
Order By: Relevance
“…Antisense clone as28 also grew slowly compared to wild-type 2008 while ASNA1 overexpressing clone s18 and the empty vector control displayed similar doubling times (Table I). wild-type and also resistant to antimonite and arsenite (4). To evaluate if ASNA1 is involved in RASP (Resistance to As, Sb and Pt), the ASNA1 expression in 2008/A was measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antisense clone as28 also grew slowly compared to wild-type 2008 while ASNA1 overexpressing clone s18 and the empty vector control displayed similar doubling times (Table I). wild-type and also resistant to antimonite and arsenite (4). To evaluate if ASNA1 is involved in RASP (Resistance to As, Sb and Pt), the ASNA1 expression in 2008/A was measured.…”
Section: Resultsmentioning
confidence: 99%
“…One important mechanism for resistance is reduction of intracellular platinum levels (3). Cisplatin resistant cells exhibit not only a low platinum content, but also a decreased accumulation of arsenite (4). These cells are cross resistant to arsenite, antimonite and cisplatin, termed the RASP-phenotype (Resistance to As, Sb and Pt) (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has shown that mechanisms involved in copper homeostasis play important roles in platinum transportation through cells (Komatsu et al, 2000;Ishida et al, 2002;Samimi et al, 2003). One of the earliest hints that copper homeostasis mechanisms might be involved in resistance to the platinum drugs was the observation that cells resistant to platinum drugs are cross-resistant with other metal or metalloid-containing agents (Naredi et al, 1995;Shen et al, 1998). In our oxaliplatin model, we found that S3 cells were cross-resistant to copper sulphate and arsenic trioxide (resistance index, 2 and 4.7, respectively) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Certain cisplatin-resistant cell lines demonstrate cross-resistance to metals that include cadmium, antimony and arsenite (19). The identification of cross-resistant metals aids the evaluation of the mechanism underlying cisplatin resistance and metal transport systems.…”
Section: Discussionmentioning
confidence: 99%